The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.palaeo.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The Early Holocene palaeoenvironment of Ounjougou (Mali): Phytoliths in a multiproxy context

Abstract: a b s t r a c t a r t i c l e i n f oThe site complex Ounjougou on the Dogon Plateau (Mali) comprises sediments up to 100,000 years old with numerous Pleistocene and Holocene sequences. The site Ravin de la Mouche (11.4-10.2 ka) is of special archaeological significance because in its Early Holocene deposits, pottery sherds have been found which are among the oldest in Africa. For a better understanding of the environmental conditions which might have contributed to the innovation of pottery making, a multi-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 77 publications
0
49
0
2
Order By: Relevance
“…Because phytoliths are normally well preserved in oxidizing environments, their morphological assemblages have been widely used for paleo-environmental reconstructions and archaeological and paleontological research (e.g., Piperno and Becker, 1996;Alexandre et al, 1999;Prebble et al, 2002;Prasad et al, 2005;Bremond et al, 2005Bremond et al, , 2008aPiperno, 2006;Alam et al, 2009;Neumann et al, 2009;Rossouw et al, 2009). In parallel, quantification of phytoliths in plants, soils, and rivers has been used to study the biogeochemical cycle of silica, which itself is coupled to the global C cycle (Blecker et al, 2006;Struyf et al, 2009;Cornelis et al, 2011;Alexandre et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Because phytoliths are normally well preserved in oxidizing environments, their morphological assemblages have been widely used for paleo-environmental reconstructions and archaeological and paleontological research (e.g., Piperno and Becker, 1996;Alexandre et al, 1999;Prebble et al, 2002;Prasad et al, 2005;Bremond et al, 2005Bremond et al, , 2008aPiperno, 2006;Alam et al, 2009;Neumann et al, 2009;Rossouw et al, 2009). In parallel, quantification of phytoliths in plants, soils, and rivers has been used to study the biogeochemical cycle of silica, which itself is coupled to the global C cycle (Blecker et al, 2006;Struyf et al, 2009;Cornelis et al, 2011;Alexandre et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoliths are good indicators to trace the existence of true tropical forest environments in tropical Africa (Fig. 4) (Bremond et al, 2005a;Aleman et al, 2011) but, conversely, they still fail to reconstruct the ligneous cover in tropical savanna environments (Neumann et al, 2009;Novello et al, 2012). As a result, the Bol phytolith data cannot provide much information on the presence/abundance of the ligneous cover in these paleo-savannas.…”
Section: Tropical Savanna As the Dominant Biome In The Basinmentioning
confidence: 99%
“…9) currently occurring in the Lake Chad basin (Gaston, 1996). Some authors (Neumann et al, 2009;Prasad et al, 2011), however, asserted to have identified a specific bilobate type -"the bilobate type with scoped ends" -which they described as diagnostic of the Ehrhartoideae grass subfamily. The description criteria and classification used in this study were not designed to specifically isolate this bilobate type that may have thus be counted as part of the bilobate types with notched ends (Bi8 type) (see Table 3 for Bi-8 type photograph), which in fact probably include a larger morphological variability than the bilobate type with scoped ends itself.…”
Section: Lesson For the Pliocene Grass Expansion In Central Africamentioning
confidence: 99%
“…The rainy season contributed to rambling flow with strong competence in a wide sandy gravel bed while the dry season led to decantation deposits in permanent pools as shown by the absence of desiccation evidence at the top of the fine deposits attributable to the dry season. Moreover, for the first time in the sedimentation, the abundance and nature of organic material evidences the importance of the vegetal cover in the valley base (riverain) and slopes (Eichhorn and Neumann, 2007;Neumann et al, 2009). This indicates the transition to a calmer river system that can be explained by the reconquest of vegetation on the slopes and in the base of the valley, limiting the sedimentary contribution to the talweg.…”
Section: Methodsmentioning
confidence: 99%